The olfactory functional network in the Alzheimer’s disease continuum: a resting state fMRI study - Ballotta, Daniela; Casadio, Claudia; Tondelli, Manuela; Zanelli, Vanessa; Ricci, Francesco; Carpentiero, Omar; Lui, Fausta; Filippini, Nicola; Chiari, Annalisa; Molinari, Maria Angela; Benuzzi, Francesca (Frontiers in Aging Neuroscience, 2026)
IntroductionOlfactory dysfunction is common in the Alzheimer’s Disease continuum, and olfaction may be altered before clinical syndrome onset. The present study aimed at investigating the functional connectivity of the olfactory cortex and its correlation with olfaction performance in a group of patients with Mild Cognitive Impairment (MCI) who subsequently converted or not converted to Alzheimer’s Disease (AD) dementia.MethodsAt baseline, 30 MCI patients were evaluated with the Sniffin’ Sticks (threshold, discrimination, and identification) to assess olfactory capacities, and they were followed up over time to identify converter and stable patients. Resting-state fMRI data acquired at baseline were analyzed to assess functional connectivity of left and right olfactory cortex. Beta values were extracted from the stable versus converter contrasts and correlated with olfactory scores.ResultsFunctional connectivity of the olfactory cortex was significantly increased with the posterior cingulate cortex, and significantly decreased with middle cingulate cortex, supplementary motor area, and left pre- and postcentral gyri, in converter compared to stable patients. Reduced negative functional connectivity between olfactory cortex and left angular gyrus emerged in converter patients, and a negative correlation was found between angular gyrus and discrimination scores.DiscussionOur findings indicate alterations of functional connectivity of the olfactory cortex in subjects with MCI at risk of conversion to AD dementia, even at the early stages of the disease. Additionally, the negative correlation between olfactory ability and the angular gyrus functional connectivity, a cerebral region known to be involved in multisensory integration processing, may be considered as a marker of disease progression.